Impact and Effect of Gamification in Islamic Religious Education (PAI): Its Implications for Motivation, Engagement, Learning Culture, and Educational Equity - Akmila, Anggun; Sarif, Muhammad Maulana Alfin (JOIES (Journal of Islamic Education Studies), 2026)
21st-century learning requires innovative strategies to ensure that the learning process remains meaningful. One emerging approach is gamification, which involves the application of game elements such as points, badges, and leaderboards in an educational context. However, research on gamification in Islamic Religious Education tends to focus on improving overall learning outcomes and has not yet extensively examined the mechanisms through which gamification can enhance student motivation and engagement in the learning process. This article aims to examine the impact of gamification on student motivation and engagement in learning, as well as its implications for changes in learning behavior, learning culture, and educational equity from the perspective of Islamic Religious Education. This study employs a qualitative approach using a literature review method. Data sources were drawn from relevant, accredited national journal articles on the topic. The results of this study are as follows: 1) gamification significantly enhances students’ learning motivation and engagement by reinforcing both intrinsic and extrinsic motivation; 2) there was a significant change in students’ learning behavior following the implementation of gamification, as evidenced by increased participation, interaction, discipline, and enthusiasm in the learning process; 3) Gamification has implications for fostering a more interactive and collaborative learning culture, while also serving as a primary tool to enhance equity. The effectiveness of gamification is influenced by instructional design, the suitability of digital media, and teachers’ ability to integrate game elements with the learning objectives. However, the implementation of gamification also has the potential to foster an unhealthy culture of competition and disparities in participation if it is not designed pedagogically and equitably. Therefore, gamification needs to be developed with consideration for Islamic values, the principle of equity, and the orientation toward character development of students.